Pharmacogenetics: A precision medicine approach to combatting the opioid epidemic. Issue 2 (30th December 2021) - Smith, D. Max; Stevenson, James M.; Ho, Teresa T.; Formea, Christine M.; Gammal, Roseann S.; Cavallari, Larisa H.
Abstract: Ineffective pain control is the most commonly cited reason for misuse of prescription opioids and is influenced by genetics. In particular, the gene encoding the CYP2D6 enzyme, which metabolizes some of the most commonly prescribed opioids (eg, tramadol, hydrocodone) to their more potent forms, is highly polymorphic and can lead to reduced concentrations of the active metabolites and decreased opioid effectiveness. Consideration of the CYP2D6 genotype may allow for predicting opioid response and identifying patients who are likely to respond well to lower potency opioids as well as those who may derive greater pain relief from nonopioid analgesics vs certain opioids. There is emerging evidence that a CYP2D6 ‐guided approach to pain management improves pain control and reduces opioid consumption and thus may be a promising means for combating opioid misuse. Clinical practice guidelines are available for select opioids and other analgesics to support medication and dose selection based on pharmacogenetic data. This article describes the evidence supporting genotype‐guided pain management as a means of improving pain control and reducing opioid misuse and clinical recommendations for genotype‐guided analgesic prescribing. In addition, a "how to" guide using patient case examples is provided to demystify the process for implementing pharmacogenetics‐guided pain management to optimize analgesia and minimize adverse effects. Optimizing pain management through genotype‐guided approaches may ultimately provide safer and more effective therapy for pain control while decreasing the risk for opioid misuse.